Dinamika Perkembangan Bank Syariah di Asia Tenggara : Antara Malaysia dan Brunei Darussalam - Safiratul Ulya; Shochibul Fandillah; Kharis Fadlullah Hana (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
The development of Islamic banking continues to show significant progress, with Southeast Asia becoming the main growth center of the Islamic financial sector in the world. Each Islamic bank has its own characteristics and advantages in various aspects of performance. This study aims to compare the financial performance between Islamic banks in Malaysia and Brunei Darussalam. The study population includes Islamic banks from both countries, with samples taken from Maybank Islamic Berhad and Bank Islam Brunei Darussalam. Measurement of financial performance is carried out through profitability analysis. The approach used is quantitative with descriptive statistical analysis and One Sample t-test using SPSS software. The test results show significant differences in the ROA, ROE, CAR, and BOPO ratios between the two banks. The research findings reveal that Maybank Islamic Berhad has better performance in the BOPO and ROE ratios, while Bank Islam Brunei Darussalam excels in the ROA ratio, also enriching the understanding of the differences in operational dynamics and financial conditions of Islamic banks in two countries with different economic and regulatory characteristics. This study is expected to be an evaluation material to improve the performance of each Islamic bank.